2010
DOI: 10.1007/s11126-010-9131-5
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Applicability of the Self-Appraisal of Illness Questionnaire (SAIQ) to Chronic Schizophrenic Patients in Taiwan

Abstract: Over the last decade, several self-report instruments to assess insight of illness from schizophrenic patients' perspectives have been administered. The main purpose of this study was to ascertain the reliability and validity of the Taiwanese version of the Self-Appraisal of Illness Questionnaire (SAIQ) in a chronic schizophrenic sample in Taiwan. This scale is a self-administered instrument designed to evaluate attitudes toward mental illness among patients receiving treatment. In the current cross-sectional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 24 publications
2
6
0
Order By: Relevance
“…We administrated the insight and judgement item (G12) of the Positive and Negative Syndrome Scale (PANSS; Kay et al 1987), which provides a rating of 1 to 7 based on the global awareness of illness symptoms, need for treatment and consequences of illness. Insight was also assessed using the Chinese version (Kao & Liu, 2010) of the Self-Appraisal of illness Questionnaire (Marks et al 2000), a self-report 17-item insight scale. This scale contains three subscales: the worry, need for treatment and presence/outcome of illness.…”
Section: Methodsmentioning
confidence: 99%
“…We administrated the insight and judgement item (G12) of the Positive and Negative Syndrome Scale (PANSS; Kay et al 1987), which provides a rating of 1 to 7 based on the global awareness of illness symptoms, need for treatment and consequences of illness. Insight was also assessed using the Chinese version (Kao & Liu, 2010) of the Self-Appraisal of illness Questionnaire (Marks et al 2000), a self-report 17-item insight scale. This scale contains three subscales: the worry, need for treatment and presence/outcome of illness.…”
Section: Methodsmentioning
confidence: 99%
“…Its Need for Treatment and Presence/Outcome of Illness subscales have been used as brief screening instruments for schizophrenic patients who may be at risk for treatment noncompliance [33]. The Taiwanese version of the SAIQ [34] is a selfreported instrument composed of 17 items in which participants are asked to rate the extent to which they agree with each statement using a four-point Likert scale, ranging from 0 (i.e., ''do not agree at all'') to 3 (i.e., ''agree completely''). The internal consistency of the Taiwanese version of the SAIQ is 0.867 and the test-retest reliability is 0.8 [34].…”
Section: Methodsmentioning
confidence: 99%
“…The Taiwanese version of the SAIQ [34] is a selfreported instrument composed of 17 items in which participants are asked to rate the extent to which they agree with each statement using a four-point Likert scale, ranging from 0 (i.e., ''do not agree at all'') to 3 (i.e., ''agree completely''). The internal consistency of the Taiwanese version of the SAIQ is 0.867 and the test-retest reliability is 0.8 [34]. Lower SAIQ subscale scores indicate decreased a patient's awareness of psychiatric illness.…”
Section: Methodsmentioning
confidence: 99%
“…A review of the literature indicates that clinical insight is associated with depression in patients with psychosis [33,39-41]; however, the findings of studies examining the relationship between cognitive insight and depression have been mixed. Two studies [33,37] found a correlation between depression as measured by the Beck Depression Inventory-II (BDI-II) and cognitive insight in patients with schizophrenia or schizoaffective disorder; however, another study [24] did not find such a correlation in individuals with psychotic disorders.…”
Section: Introductionmentioning
confidence: 99%